Computer modelling of innovations relative to Latin in contemporary Romance dialects - Philippe Boula de Mareüil; Marc Evrard; Alexandre François; Antonio Romano (Isogloss)
This study relies on a corpus illustrating several dozen Romance dialects from France, Belgium, Switzerland, Italy, Spain and Portugal, for which 145 innovations relative to Latin have been encoded in the form of 1 (presence) or 0 (absence). Based on contemporary recordings (translations of Aesop’s 100-word fable “The North Wind and the Sun” and another 100-word list), following the principles of dialectometry, the Comparative method and especially historical glottometry, we propose computational tools to address the relationships and classifications amongst these Romance varieties. Results of data-mining techniques confirm the robustness of a North/​South divide — with the Oïl area being, by far, the most innovative — and, secondarily, an opposition between the South-West (mainly Ibero-Romance) and the South-East (mainly Italo-Romance, more conservative). Among the most important/​discriminant features are the palatalisation of Latin ca, which characterises the majority of northern Gallo-Romance dialects, and the simplification of geminates north of the La Spezia-Rimini line. Most innovations relate to phonetic/​phonological traits. However, we also consider morphosyntactic and lexical features, such as non-null subject in northern Gallo-Romance varieties, and the substitution of cum ‘with’ by apud > amb in Occitano-Romance varieties. By retaining only morphosyntactic innovations, we still find a North vs. South-East- vs. South-West tripartition.